2014
DOI: 10.1007/s13749-014-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cigarette smoking on the plasma fatty acid profile and their interaction in determining the burden of subclinical atherosclerosis

Abstract: IMT were measured in 36 smokers and 36 neversmokers, matched for age, sex and lipid levels.Compared to never-smokers, smokers had higher saturated FA (14:0, 16:0) and monounsaturated FA (16:1, 18:1) levels and lower levels of 24:1, arachidonic acid, docosahexaenoic acid, total polyunsaturated fatty acids and n-3. Endogenously generated FA (e.g., docosapentaenoic acid) and the Δ5 Desaturation Index were also reduced in smokers. In partial correlation analysis of the whole series of 72 subjects, after adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Finally, we show that smoking had a strong effect on the plasma lipidome. Our observations of negative associations with lipids containing polyunsaturated fatty acids, particularly omega-3 species such as DHA (C22:6), and positive association with saturated or monounsaturated species agree with previous reports [83,84]. Smoking modulates essential fatty acid metabolism and results in a reduction of polyunsaturated fatty acid levels through depletion of antioxidants and subsequent increase in lipid peroxidation [85].…”
Section: The Association Of Bmi and Smoking With The Plasma Lipidomesupporting
confidence: 92%
“…Finally, we show that smoking had a strong effect on the plasma lipidome. Our observations of negative associations with lipids containing polyunsaturated fatty acids, particularly omega-3 species such as DHA (C22:6), and positive association with saturated or monounsaturated species agree with previous reports [83,84]. Smoking modulates essential fatty acid metabolism and results in a reduction of polyunsaturated fatty acid levels through depletion of antioxidants and subsequent increase in lipid peroxidation [85].…”
Section: The Association Of Bmi and Smoking With The Plasma Lipidomesupporting
confidence: 92%
“…These results confirm recent findings in the omega-3 index in erythrocyte or in total n-3 in serum fatty acid [12][13][14][15]17,53]. This influence is possibly caused by the adverse effect of smoking on the conversion process of ALA to DHA [54,55]. This link with DHA and n-3 was not observed in T3, probably by the mechanism of transferring DHA maternal stores to foetus.…”
Section: Discussionsupporting
confidence: 90%
“…This link with DHA and n-3 was not observed in T3, probably by the mechanism of transferring DHA maternal stores to foetus. However, it was shown that smoking increased the n-6/n-3 ratio, which suggests that smoking could affect the fatty acid profile some another way since it might alter the conversion rate of n-6 to eicosanoids, such as prostaglandin E2 [55,56]. This shows an anti-inflammatory effect and has a crucial role in the regulation of delivery [57].…”
Section: Discussionmentioning
confidence: 99%
“…Smoke exposure has been shown to increase FA oxidation through reduced levels of circulating polyunsaturated FA (PUFA) along with other inflammatory processes . Baldassarre et al outlined the mechanism of smoking‐induced changes of plasma FA that consequently enhanced peroxidative processes. It has been postulated that an increase in smoke exposure increases FA levels in cellular cytosol, resulting in protection against lipotoxicity.…”
Section: Metabolomic‐driven Discovery Of Biomarkersmentioning
confidence: 99%
“…It has been postulated that an increase in smoke exposure increases FA levels in cellular cytosol, resulting in protection against lipotoxicity. Conversely, impaired carnitine metabolism in COPD can cause accumulation of FA in the cytosol which can also lead to lipotoxicity . Metabolomics in COPD provides insight into the pathogenesis of the disease with alterations in sphingolipid metabolism and changes in lipids during increased oxidant stress.…”
Section: Metabolomic‐driven Discovery Of Biomarkersmentioning
confidence: 99%